Effect of nitriding on microstructure and wear behavior of HVOF sprayed AlxCoCrFeNi (x= 0.4, 0.7, 1.0) high-entropy alloy coatings. (December 2022) - Zhou, Yong-kuan; Kang, Jia-jie; Zhang, Jie; Zhu, Shuo; Fu, Zhi-qiang; Zhu, Li-na; She, Ding-shun
Abstract: In order to investigate the effect of nitriding on wear performance of (High Velocity Oxygen Fuel) HVOF sprayed high-entropy alloy (HEA) coatings, the Alx CoCrFeNi (x = 0.4, 0.7, 1.0) coatings were prepared via HVOF technology on AISI 4135 steel firstly, and then were treated by plasma nitriding. The reciprocating friction and wear experiments with Si3 N4 grinding ball of Alx CoCrFeNi HEA coatings with un-nitrided and nitrided were carried out. The microstructure, phase compositions and microhardness of the coatings were studied. The effect of nitriding treatment on the wear performance of the coatings was also discussed. The results show that HVOF sprayed Alx CoCrFeNi HEA coatings have compact structure. With the increase of Al content, the coatings change from FCC phase to BCC phase. Besides, the microhardness and wear resistance of the coatings increase with the increase of Al content. After nitriding, the coatings exhibit FCC phase and various nitride phases (mainly AlN and CrN), and the microhardness values of the coatings are approximately twice that of un-nitrided coatings. The nitrided coatings show the better wear resistance than the un-nitrided coatings, although both of them have good wear resistance. The HVOF sprayed AlCoCrFeNi HEA coating with nitrided has the best wear resistance. The wear mechanism of un-nitrided coatings is as follows: it is abrasive and adhesive wear with x = 0.4, the adhesive wear becomes serious with x = 0.7, and it is tribo-oxidation wear and slight abrasive wear with x = 1.0, respectively. For the wear mechanism of nitrided coatings: it is mainly abrasive wear with x = 0.4, it is abrasive wear and adhesive wear with x = 0.7, and it is tribo-oxidation wear and abrasive wear with x = 1.0, respectively. Highlights: Alx CoCrFeNi (x = 0.4, 0.7, 1.0) high-entropy alloy coatings were prepared by HVOF. The coatings were treated by plasma nitriding. The un-nitrided coatings have good wear resistance. The wear resistance of nitrided coatings are more excellent.